Synthesis of Solketal Fuel Additive From Acetone and Glycerol Using CO2 as Switchable Catalyst - Nascimento, Júlia A. C.; Pinto, Bianca P.; Calado, Verônica M. A.; Mota, Claudio J. A. (Frontiers in Energy Research, 2019)
The production of solketal fuel additive was studied from the reaction of glycerol and acetone in the presence of pressurized CO2 as switchable catalyst. A design of experiments (DoE) was used to study the significance of temperature, initial pressure of CO2, glycerol/acetone molar ratio, and reaction time. The response variable was the glycerol conversion that was analyzed by GC-MS. Temperature, reaction time and initial pressure of CO2 were statistically significant whereas the molar ratio of glycerol/acetone was not. The maximum conversion at the optimal conditions (118°C, 42 bar and 5 h) was 61%. Reactions with glycerol doped with common contaminants present in the glycerin of biodiesel production was also carried out. Water has a drastic effect on the conversion, as well as the concomitant addition of water and NaCl. Reactions with a glycerin of biodiesel production, using NaOH or Ba(OH)2 as catalyst of transesterification, gave 6 and 20% conversion, respectively.